AGARICOMYCETES MUSHROOMS DISTRIBUTED IN ARMENIA – SOURCE OF COSMETIC BIOINGRЕDIENTS (Proceedings of the YSU B: Chemical and Biological Sciences, 2022)
Currently, the cosmetic industry is in a constant search for valuable bioingredients with anti-aging (antioxidant, anti-inflammatory, anti-collagenase, anti-elastase, anti-hyaluronidase and anti-tyrosinase) properties. Edible and medicinal Agaricomycetes mushrooms (macrofungi) as unlimited source of bioactive compounds and enzymes have mainly been studied for their nutritional value and medicinal properties. They have also been included in cosmetic formulations for topical and oral administration however there is slow progress in their usage as cosmeceuticals.We described 19 medicinal, including 12 edible mushrooms belonging to 18 genera of Agaricomycetes fungi distributed in Armenia – as potential cosmeceuticals. Further evaluation of mushrooms resources in Armenia will revealed new species and promote their biotechnological exploitation not only as mushroom-derived nutraceuticals and pharmaceuticals, but also cosmeceuticals. Advances in biology and biotechnology of Agaricomycetes will further assist development of myco-cosmetology in Armenia.
Keywords: Agaricomycetes; anti-aging; bioactive compounds; cosmeceuticals; enzyme inhibitors; mushrooms